Використання технології NFC для автоматизації ведення обліку товарів - Колісник, Т. Б. (ХНУРЕ, 2021)
In the article the areas of application of the NFC have been considered. Goals of the NFC forum have been analyzed. Three modes of NFC operation have been described: emulation, reading, P2P. Active and passive types of interaction have been analyzed. Goals of the automated system with using NFC technology have been considered.
Keywords: технологія NFC; автоматизація ведення обліку товарів